Penilaian Kualitas Desain Perguruan Tinggi dengan Menggunakan Pendekatan CPTED di Kota Semarang - Dini Oktaviani Hapsari; Retno Susanti (Ruang, 2019)
The existence of Undip and Unika in Semarang become the main attraction for students who are outside Semarang. It can increase the activity around Undip and Unika areas. Nevertheless, there are some new things happening around the campus area, in September 2017, there were reports of loss of 34 motorcycles, 133 helmets and 1 rearview mirror in Undip. Meanwhile, Unika has a case of murder that killed a man outside the exit gate of Unika in 2014. Therefore to minimize the crime case it is necessary to "Crime Prevention through Environmental Design (CPTED)" in campus area, can improve students' sense of security on the two campuses. In this research, to achieve the result of design quality, the method of analysis used is descriptive quantitative method. Analytical technique used is Analytical Hierarchy Process (AHP) and scoring using categorical given in the form of descriptive quantitative. Results of research that determine in Undip are in the sufficient category with 2,079 and the Unika category is in good category with a score of 2,378. These differences can be influenced by factors such as land area, contour, building density, area, number of students, and number of activities, which can cause facilities and policies to reduce crime and improve security at Undip and Unika.